APPLICATION OF THE DESIGN METHOD IN TEACHING PHYSICS AT SCHOOL - Rystygulova, В.Б.; Zhaksylykova , А.К. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The article presents a real example of research of a scientific project using one of the methods of innovative pedagogical technologies. The model of application of the project method to research works of schoolchildren in physics is obtained. The scientific project model contains the design algorithm, SMART project goal, brief description of the project, and the result of training in the design method. A scientific project on the topic «Research of the radiation spectrum of artificial light sources» is considered. For the analysis of the radiation spectrum, 5 light sources were selected, which are manufactured commercially and are used for lighting. Studies of radiation spectra were carried out on a special installation. Analyzing the spectral lines of the selected light sources, it is proposed to construct a radiation source from LEDs of different colors. It is recommended that subject teachers use the design method for each new physics topic for students in grades 5-9 to develop their project skills.